Optimal acute care of the older adults: Are we ready to open the Pandora box? - Shrestha, Roshana (Journal of General Practice and Emergency Medicine of Nepal, 2021)
The emergency departments (ED) present as the gateway to healthcare services for an increasing number of older adults. Acute care of this vulnerable population in a busy ED presents its own unique challenge. They have higher mortality in the hospital and following discharge, a higher revisit rate to the ED, and are at a higher risk of functional decline following an ED visit. Extra caution and mindfulness are needed when caring for them as they differ from younger patients in several ways. This article tries to put forward feasible strategies with an integral and holistic view to meet their complex need in the ED.